2016
DOI: 10.1007/s12639-016-0772-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of cutaneous leishmaniasis species by PCR–RFLP in Ilam province, the west of Iran

Abstract: Cutaneous leishmaniasis (CL) is one of the most common parasitic diseases and public health problems in Iran. CL is endemic in most parts of Ilam province, in the west of Iran. The distance from the center of country, the great number of divers rural areas, and lack of specialists and laboratory facilities have been the major causes of Leishmania species remaining unknown in this region. Polymerase chain reaction followed by restriction fragment length polymorphism was performed to identify the Leishmania spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…Ilam province, sandwiched between Kermanshah and Khuzestan provinces and Iraq, is also endemic for L. major. Two studies in Ilam and Mehran counties showed that all CL cases (n = 61/61 and n = 92/92, respectively) were infected by L. major (56,57).…”
Section: Western Iranmentioning
confidence: 99%
“…Ilam province, sandwiched between Kermanshah and Khuzestan provinces and Iraq, is also endemic for L. major. Two studies in Ilam and Mehran counties showed that all CL cases (n = 61/61 and n = 92/92, respectively) were infected by L. major (56,57).…”
Section: Western Iranmentioning
confidence: 99%
“…A long border with Iraq, where no controls exist over leishmaniasis due to war and political problems, has resulted in an increased number of CL cases. A close distance to endemic CL foci such as Bushehr, Ilam, and Isfahan provinces affects new foci in Khuzestan province (16)(17)(18)(19). Several studies have been carried out in Khuzestan to molecularly characterize Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, o uso de urina a 5% colhida de pacientes nefropatas com diabetes mellitus induziu a uma maior curva de crescimento. Possivelmente, a proteinúria que ocorre nesses pacientes pode ter servido como fonte de aminoácidos, principais moléculas utilizadas para obtenção de energia pelo protozoário (SHAMSUZZAMAN et al, 1999 major confirmados por PCR-RFLP (KERMANJANI et al, 2017).…”
Section: Discussionunclassified